MODIFIKASI DONGKRAK BOTOL DAN TREKER UNTUK MELEPAS BEARING MOTOR LISTRIK - Ismael Marjuki; Helanianto Helanianto; Betti Ses Eka Polonia (Injection: Indonesian Journal of Vocational Mechanical Engineering, 2022)
This research modifies the bottle jack to remove the electric motor bearing of a water pump with a jack capacity of 2 tons. Bottle jacks are generally used to lift vehicles such as cars. The bottle jack can be modified so that it can be used as a bearing removal device. In general, the way to remove the bearing is still manual, namely by hitting it. The purpose of making this tool is to make it easier to remove the water pump electric motor bearing. The specifications of the tool are that it has a height of 16 - 27 cm. The width of the tool is 6 cm and the maximum pressure capacity of the bottle jack is 2 tons. The trial results of the bottle jack modification tool to remove the water pump electric motor bearings obtained an average time of 45 seconds.